Psychosocial and pharmacological treatments for cannabis use disorder and mental health comorbidities: a narrative review. Issue 3 (4th February 2021) - Lees, Rachel; Hines, Lindsey A.; D'Souza, Deepak Cyril; Stothart, George; Di Forti, Marta; Hoch, Eva; Freeman, Tom P.
Abstract: Cannabis is the most widely used illicit drug worldwide, and it is estimated that up to 30% of people who use cannabis will develop a cannabis use disorder (CUD). Demand for treatment of CUD is increasing in almost every region of the world and cannabis use is highly comorbid with mental disorders, where sustained use can reduce treatment compliance and increase risk of relapse. In this narrative review, we outline evidence for psychosocial and pharmacological treatment strategies for CUD, both alone and when comorbid with psychosis, anxiety or depression. Psychosocial treatments such as cognitive behavioural therapy, motivational enhancement therapy and contingency management are currently the most effective strategy for treating CUD but are of limited benefit when comorbid with psychosis. Pharmacological treatments targeting the endocannabinoid system have the potential to reduce cannabis withdrawal and cannabis use in CUD. Mental health comorbidities including anxiety, depression and psychosis hinder effective treatment and should be addressed in treatment provision and clinical decision making to reduce the global burden of CUDs. Antipsychotic medication may decrease cannabis use and cannabis craving as well as psychotic symptoms in patients with CUD and psychosis. Targeted treatments for anxiety and depression when comorbid with CUD are feasible.